QUERCETIN DERIVATIVES DOCKING BASED ON STUDY OF FLAVONOIDS INTERACTION TO CYCLOOXYGENASE-2 - Rahmana Emran Kartasasmita; Rina Herowati; Nuraini Harmastuti; Tutus Gusdinar (Indonesian Journal of Chemistry, 2009)
Due to their ability to inhibit cyclooxygenase-2 (COX-2), certain flavonoids show anti-inflammatory effects. Quercetin is a flavonoid suitable to be chosen as the lead compound for development of safe anti-inflammatory agent, because in addition to its anti-inflammatory effect, quercetin shows also protective effect in gastrointestinal track. The objective of this research is to study the binding modes of certain flavonoids and predict the quercetin derivatives inhibiton activity on COX-2 by means of docking method using ArgusLab 4.0.1 software. Some flavonoids (7-hydroxyflavone, apigenin, galangin, kaempferol, quercetin, naringenin and daidzein) and quercetin derivatives were used as ligands for docking study. The COX-2 structure was obtained from Brookhaven protein databank. After assigning hydrogen atoms and charges, computational docking was performed. The docking results were evaluated based on the binding energy and hydrogen bonding of  the ligands on binding site of COX-2. A curve constructed by plotting binding energy versus logarithm of IC50 of flavonoids shows a good correlation with a regression equation of log IC50 = 0.8069 ΔGbind + 9.4456(r = 0.9226; P50 values of the quercetin derivatives were calculated. The predicted IC50 values of quercetin-3-O-acetate; 6-chloroquercetin,3-O-acetate; 6,8-dibromoquercetin; 6,8-dichloroquercetin-3-O-acetate and 6,8-dibromoquercetin-3-O-acetate are lower than thats of quercetin. These results show that only substitutions at certain position on quercetin with acetyl group, chlorine and bromine atoms increase the inhibitory activity of quercetin against COX-2.